Antimicrobial producing microbes isolated from soil samples collected from Nanga Merit Forest in Sarawak, Malaysian Borneo - Samuel, Lihan; Chai, Sin Lin; Ismail, Ahmad; Fazia, Mohamad Sinang (Pelagia Research Library, 2014)
This study was carried out to screen for potential antimicrobial producing microbes from soil samples collected from Nanga Merit forest. After primary and secondary screening, one bacterial isolate (B17) and four fungal isolates (F10, F11, F14 and F26) produced antimicrobial activity against Staphylococcus aureus, Salmonella typhi, Escherichia coli and Enterobacter aerogenes. The minimal inhibition concentration (MIC) of the methanol extract from isolate B17 against the four tested bacteria was determined by disk-diffusion and agar well diffusion methods. The MIC values when tested against S. aureus, S. typhi, and E. coli were 25μg/μl whereas the MIC value was 12.5μg/μl when tested against E. aerogenes. In the agar well diffusion method, the respective MIC values were < 1.5625μg/μl for S. aureus, 12.5 μg/μl for both the S. typhi and E. coli, and 9.375 μg/μl for E. aerogenes. Besides, extracts from F26 cultivated on PDA, CDA, and V8 juice agar showed weak activity against E. aerogenes and was not tested further for its MIC values. The extract from B17 also exhibit antifungal activity when tested against test fungus (Fusarium sp.). Fungal isolates (F10, F11, F14 and F26) cultivated on PDA exhibited great antifungal activities.